ANALYSIS OF STUDENTS' SLEEP DURATION IN INCREASING STUDENTS' MOTIVATION TO LEARN AT SCHOOL (Case Study of Students at Islamic Boarding Schools) - suryani, irma; Mhd. Subhan; M.Idkam Khalid3; Amin Ma’sum; Khairunnas Rajab (Mathematics Research and Education Journal, 2024)
This study aims to analyze the influence of sleep duration on the formation of students' learning motivation at SMPIT IBS Riau through a qualitative approach. The research method employed was a case study with data collection techniques including in-depth interviews, observations, and document analysis. Participants were purposively selected from mentoring teachers, academic teachers, and students at SMPIT IBS Riau. The research findings indicate a variety of sleep duration among students. Some students adhere well to sleep regulations, while others frequently fall short of the recommended duration. Students with adequate sleep patterns reported feeling more energetic, focused in their studies, and highly motivated, whereas those with inadequate sleep patterns experienced quick fatigue and difficulty concentrating. Factors such as family habits, extracurricular activities, and school policies influence students' sleep duration. The study concludes that sufficient sleep duration plays a crucial role in shaping students' learning motivation at SMPIT IBS Riau during classroom learning processes.